Combating Corruption in Bangladesh: An Unexplored Framework in Anti-Corruption Strategies - Md. Yasir Arafat Arman; Mohammad Faruq Azam (Journal of Arts, Humanities and Social Science)
From the colonial past to the post-independence period, corruption has been a revolving problem in Bangladesh, endangering governance, economic growth, and social justice. Despite substantial institutional and legislative reforms, the country continues to experience high levels of bribery, embezzlement, and political graft, as reflected by its low rankings on global corruption indices. While punitive measures and bureaucratic changes are the major focus of current anti-corruption strategies, the potential of Islamic ethical teachings as a supplementary paradigm is still largely unexplored in both academic and policy debates. This review paper argues that incorporating Islamic principles, which are rooted in the Qur’anic teachings, the Hadiths (sayings) of the Prophet, and historical Islamic governance models, could provide a morally and culturally effective strategy for reducing corruption in Bangladesh’s socio-political environment. This study shows how Islamic concepts of accountability (hisbah), justice (a’dl), and public trust (amanah) might support anti-corruption initiatives in Bangladesh by combining theological sources, empirical research, and policy analysis. It also examines practical implementation strategies such as faith-based accountability frameworks, mosque-based awareness programs, and Islamic social financing (zakat and waqf) for transparency. The review identifies shortcomings in existing approaches, such as their excessive dependence on secular frameworks and negligence of Bangladesh’s religious and cultural context, and offers practical suggestions for decision-makers. Furthermore, this study adds to the broader discourse about faith-based anti-corruption strategies and presents Islamic ethics as a potential but underutilized pillar in achieving SDG 16.5 (Reducing Corruption and Bribery) in nations with a majority of Muslims, such as Bangladesh.